Demographic Differences to Attitude for the Construction of Close Relations with Disabilities - Stavitskyi, Oleg (Psychological Prospects Journal, 2018)
The article presents the results of an empirical study of psychological differences in relation to intimate relationships (friendship, love, creation of a family) with disabled members of society. The analysis was carried out in the plane of residence of the person interviewed (village, urban-type settlement, towns of regional subordination, regional centers) For this purpose, the author’s methodology «Situational modeling of the attitude towards the disabled» was used, which is a set of 30 situational tasks aimed at identifying the attitude towards the disabled. It was found that only 7,2 % of the inhabitants of the cities of regional subordination allow for the establishment of close relations with the disabled. The smaller number of persons (6,4 %) who positively perceive the possibility of building close relations with the disabled were found among the inhabitants of urban-type settlements. At the same time, the possibility of dealing with a person with minor physical disabilities and working capacity was favorably evaluated. Practically the same number of inhabitants of oblast centers (4,2 %) and villages (4,4 %) allows for the establishment of close relations with the disabled in the presence of appropriate feelings. Negative assessment of the situation prevails among residents of regional centers (25,4 %). Such recipients show open disobedience to the disabled, verbal aggression, emphasize its inferiority, apply different forms of discrimination against it. A slight difference in indicators is observed among residents of urban-type settlements (23,3 %) and cities of regional subordination (22,2 %). They do not want to associate their lives with the disabled and avoid interaction with them, but do not show open hostility. Among the villagers, 19,2 % of people tend to avoid constructing close relations with the disabled.